Adapting the Evidence Academy model for virtual stakeholder engagement in a national setting during the COVID-19 pandemic. Issue 1 (20th March 2023) - Carter-Edwards, Lori; Leverty, Renee; Bilheimer, Alicia; Bailey, Lindsay; Adeshina, Bukola; Shrestha, Prabisha; Yu, Zhitong; Dave, Gaurav; Cohen-Wolkowiez, Michael; Kibbe, Warren; Corbie, Giselle
Abstract: The COVID-19 pandemic raised the importance of adaptive capacity and preparedness when engaging historically marginalized populations in research and practice. The Rapid Acceleration of Diagnostics in Underserved Populations' COVID-19 Equity Evidence Academy Series (RADx-UP EA) is a virtual, national, interactive conference model designed to support and engage community-academic partnerships in a collaborative effort to improve practices that overcome disparities in SARS-CoV-2 testing and testing technologies. The RADx-UP EA promotes information sharing, critical reflection and discussion, and creation of translatable strategies for health equity. Staff and faculty from the RADx-UP Coordination and Data Collection Center developed three EA events with diverse geographic, racial, and ethnic representation of attendees from RADx-UP community-academic project teams: February 2021 (n = 319); November 2021 (n = 242); and September 2022 (n = 254). Each EA event included a data profile; 2-day, virtual event; event summary report; community dissemination product; and an evaluation strategy. Operational and translational delivery processes were iteratively adapted for each EA across one or more of five adaptive capacity domains: assets, knowledge and learning, social organization, flexibility, and innovation. The RADx-UP EA model can be generalized beyond RADx-UP and tailored by community and academic input to respond to local or national health emergencies.